Spontaneous dyskinesia in first episode schizophrenia. Issue 1 (1st January 1999) - Puri, B K; Barnes, Thomas R E; Chapman, M J; Hutton, S B; Joyce, Eileen M
Abstract : In the west London prospective study of first episode schizophrenia, the prevalence and nature of abnormal involuntary movements were examined in 27 patients who had never received antipsychotic drugs and 36 who had been treated with such medication. Motor disturbance was assessed with rating scales designed to cover the full range of spontaneous and drug induced movement disorder. Only one person in the drug naïve group showed evidence of parkinsonism, a finding which contrasts with recent reports suggesting that spontaneous extrapyramidal signs may not be uncommon in such patients. However, according to ratings on the modified Rogers scale, 11% of the drug naïve group exhibited orofacial dyskinesia, 4% trunk and limb dyskinesia, 7% postural abnormalities, and 4% increased muscle tone. The respective figures in the closely matched medicated group were not significantly different except for increased muscle tone, which was significantly more common (25%). The proportion of drug naïve patients fulfilling criteria for tardive dyskinesia on the abnormal involuntary movements scale ranged from 4% to 11% depending on the criterion threshold score used. These findings are in accord with the notion that abnormal involuntary movements, particularly orofacial dyskinesia, represent a neuromotor component of schizophrenia.